The prototypic class Ia ribonucleotide reductase from Escherichia coli: still surprising after all these years. (22nd May 2012) - Brignole, Edward J.; Ando, Nozomi; Zimanyi, Christina M.; Drennan, Catherine L.
Abstract : RNRs (ribonucleotide reductases) are key players in nucleic acid metabolism, converting ribonucleotides into deoxyribonucleotides. As such, they maintain the intracellular balance of deoxyribonucleotides to ensure the fidelity of DNA replication and repair. The best-studied RNR is the class Ia enzyme from Escherichia coli, which employs two subunits to catalyse its radical-based reaction: β2 houses the diferric-tyrosyl radical cofactor, and α2 contains the active site. Recent applications of biophysical methods to the study of this RNR have revealed the importance of oligomeric state to overall enzyme activity and suggest that unprecedented subunit configurations are in play. Although it has been five decades since the isolation of nucleotide reductase activity in extracts of E. coli, this prototypical RNR continues to surprise us after all these years.